Heat flow of Norway and its continental shelf. (September 2015) - Pascal, Christophe
Abstract: Terrestrial heat flow influences a large collection of geological phenomena. Its determination and understanding is of prime interest for oil industry because geothermal processes impact directly maturation histories and economic potential of oil fields and reservoirs. Published systematic heat flow determinations from major oil provinces are however seldom. Robust heat flow determinations in drillholes require logging of undisturbed temperatures and intensive sampling of core material for petrophysical measurements. Temperature logging in exploration drillholes is traditionally conducted during drilling breaks or shortly after drilling, resulting in temperatures severely disturbed by mud circulation and coring is restricted to selected intervals. Alternatively, test temperatures, information from electric logs and lithological descriptions of drill cuttings can be used to overcome these limitations. The present contribution introduces new heat flow determinations based on 63 exploration drillholes from the Norwegian North Sea, the Mid Norway Margin and the Barents Shelf. Our analyses are based on released DST temperatures, precise lithological descriptions of drill cuttings, previously measured rock matrix thermal conductivities and established porosity laws. For the sake of comparison, we carefully review previous heat flow studies carried out both onshore and offshore Norway. Our results suggest median heat flow values of 64 mW/m 2, 65 mW/m 2 and 72 mW/m 2 for the North Sea, the Mid Norway Margin (mainly the Trøndelag Platform) and the SW Barents Shelf respectively. In detail, heat flow increases by ∼10 mW/m 2 from the southern Norwegian North Sea towards the Mid Norway Margin. This result appears to be in very good agreement with seismic tomographic studies suggesting northward thinning of the underlying mantle lithosphere. Our results together with published marine heat flow data from the Mid Norway Margin suggest a gradual decrease in heat flow levels from both the North Sea and the Trøndelag Platform towards the centres of the deep Møre and Vøring basins. This latter effect is attributed to reduced heat input from crustal sources caused by the extreme attenuation of the crystalline basement below these two basins. Heat flow in the SW Barents Shelf increases westwards. This is interpreted as lateral heat transfer from the adjacent young ocean. Tentative corrections for Quaternary sedimentation/erosion effects suggest similar heat flow levels for the three studied areas but the above mentioned regional trends remain unchanged. Highlights: Heat flows are 64, 65 and 72 mW/m 2 for three domains of the Norwegian Shelf. Heat flow increases by ∼10 mW/m 2 across the North Sea. Heat flow decreases towards the centres of the deep Møre and Vøring basins. Heat flow in the SW Barents Shelf increases westwards. Corrections suggest similar heat flow levels but regional trends remain.